Transformations in health information technology and the impact on patient experience - Cynthia Sieck; Tim Huerta (The Beryl Institute, 2019)
Changes in the way we collect and use health information, and the technology that enables these processes, have transformed the patient experience in health care. Compared to an earlier focus on using health information technology (HIT) for clinical purposes, patients are now also significant users of HIT, spurring the development of Patient-Facing Health Information Technology (PFHIT). These tools allow patients to use and interact with their health information and healthcare providers is new and transformative ways. We suggest that while these transformations have significant positive impacts, there are three important considerations which must be included as HIT continues to evolve: a focus on usability of HIT tools, providing appropriate training at all levels of use, and assessing individual' patient's capacity to use such tools to alleviate disparities in use. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework. (http://bit.ly/ExperienceFramework) <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Innovation%20%26%20Technology%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens